The memoranda roll of the Irish exchequer for 3 Edward II - Craig, David Victor (Trinity College (Dublin, Ireland). Department of History, 1984)
The Irish exchequer was the financial department of the government of the king of England’s lordship of Ireland. The memoranda rolls were used to record proceedings in the exchequer and correspondence received or issued by it. Only two original rolls now survive, but there are manuscript calendars of about 150 rolls. This thesis is an edition of the earlier of the two original rolls, that for 3 Edward II (30 September 1309 - 29 September 1310, abbreviated as 1309/10). It contains the text of the memoranda roll, three appendixes, a lengthy introduction, and an index of persons and places.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin